1999
DOI: 10.1016/s0969-2126(00)80028-3
|View full text |Cite
|
Sign up to set email alerts
|

Diverse structural solutions to catalysis in a family of antibodies

Abstract: Our results demonstrate that substantial diversity may be present among antibodies catalysing the same reaction. Therefore, some of these antibodies represent different starting points for mutagenesis aimed at boosting their activity. This increases the chance of obtaining more proficient catalysts and provides opportunities for tailoring catalysts with different specificities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
1

Year Published

2001
2001
2009
2009

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 46 publications
0
18
1
Order By: Relevance
“…The binding free energy difference of 7C8, DDG ITC , was 0.4 kcal Á mol À1 , in contrast to that obtained previously for 6D9, DDG ITC ¼ 1.4 kcal Á mol À1 (Saito et al, 2005). This difference in DDG between 7C8 and 6D9 may be explained by the difference in the binding manner of the CP: the trifluoroacetyl group of CP-F is exposed to the solvent water on the surface of 7C8 while it binds deep in the hydrophobic pocket in 6D9 (Kristensen et al, 1998;Gigant et al, 1999). If in the associated state, the trifluoroacetyl group of CP-F was completely exposed without being affected by 7C8, both DH ITC and TDS ITC of CP-H binding would be similar to those of CP-F binding.…”
contrasting
confidence: 67%
See 4 more Smart Citations
“…The binding free energy difference of 7C8, DDG ITC , was 0.4 kcal Á mol À1 , in contrast to that obtained previously for 6D9, DDG ITC ¼ 1.4 kcal Á mol À1 (Saito et al, 2005). This difference in DDG between 7C8 and 6D9 may be explained by the difference in the binding manner of the CP: the trifluoroacetyl group of CP-F is exposed to the solvent water on the surface of 7C8 while it binds deep in the hydrophobic pocket in 6D9 (Kristensen et al, 1998;Gigant et al, 1999). If in the associated state, the trifluoroacetyl group of CP-F was completely exposed without being affected by 7C8, both DH ITC and TDS ITC of CP-H binding would be similar to those of CP-F binding.…”
contrasting
confidence: 67%
“…Crystal structure analyses have revealed that the two aromatic rings of CP-F are buried in the 6D9 combining site, while only the p-nitrobenzyl group is buried in the 7C8 combining site and the trifluoroacetyl group is exposed to the solvent (Kristensen et al, 1998;Gigant et al, 1999). The binding thermodynamics of 7C8 and 6D9 could be correlated with the data obtained from the crystal structure of the complexes.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations